EVALUASI KELAYAKAN BISNIS PADA PERENCANAAN USAHA: (Studi Kasus Kedai Kopi Robusta di Kota Surabaya) - Abdul Aziz; Putri Silvia; Sutikno; Vivi Dwi Yanti; Siti Nur Jannah; Nuzul Purnama (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2017)
Business is growing into one reason to obtain forecasting in the plan to realize small business activities that will be built in the outskirts of Surabaya, whether the investment in this business establishment is feasible and in a period of time some of the business can stabilize its investment. for it needs to do a research on business feasibility studies that will be reviewed from bebagai related aspects. this effort is a concept of group effort trying to sell a variety of in planning the establishment of the project with the development of a more specific menu that aims to strengthen the image of the store in efforts to gain competitive advantage from competitors around the suburbs.This business feasibility study is also to determine the amount of required investment funds, existing market share, and any constraints that may occur in the process of establishing the type of business shop. As for the objectives to be achieved from the results of this study dalah to conduct business feasibility analysis in terms of various aspects, namely market aspects, technical aspects, management aspects, financial and financial aspects, and social aspects.